Spatio-temporal-functional assembly of Daqu microbiome: Mechanistic insights and quality improvement - Rui Ma; Xiaojie Nan; Yanting Li; Yuanyu Su; Mingxia Cheng; Yujie Zhang; Yang Cui; Qiong Zhou; Jingang Gu; Shang Guo (Food Research International, 2026)

Biguanide‑modified ursolic acid as a multifunctional lipid‑mimetic carrier of DOX liposome for synergistic chemotherapy - Yanzhi Wang; Lei zhang; Panying Cui; Yanting Fan; Jiaxin Zheng; Hongmin Liu (Drug Delivery and Translational Research, 2026)

Ammonia Can Damage Hemocytes in Portunus trituberculatus by Disrupting MCU-Mediated Mitochondrial Calcium Homeostasis - Yingying Liu; Yueqi Zhang; Jianwei Cao; Chunyan Zhao; Wenqi Wang; Fang Wang; Yanting Cui; Yunliang Lu (Journal of Ocean University of China, 2026)

Silencing of the Superaquaporin LvAQP11 Disrupts Salinity Tolerance, Molting Cycle, and Myofibril Organization in Litopenaeus vannamei - Zhongkai Wang; Guanghao Song; Shikui Zhang; Long Zhang; Beibei Wang; Kunpeng Zhao; Yanting Cui; Fei Liu; Renjie Wang; Yuquan Li (Fishes, 2025)
The Pacific white shrimp (Litopenaeus vannamei), a euryhaline crustacean of significant economic importance, is widely cultivated for its adaptability to diverse salinity levels. Aquaporins (AQPs) are membrane channel proteins that mediate the transport of water and small solutes across biological membranes. Among them, aquaporin 11 (AQP11) is classified as a superaquaporin, and its physiological roles remain unclear. In this study, RNA interference (RNAi) was employed to silence AQP11 expression in L. vannamei, followed by RNA-seq analysis to investigate transcriptomic responses. Differentially expressed genes (DEGs) were identified by comparing dsAQP11 and control groups. The LvAQP11 knockdown significantly increased mortality to 76.7% under acute high-salinity stress (50‰) but not under low-salinity conditions (10‰). Transcriptomic analysis revealed that LvAQP11 deficiency disrupted amino acid metabolism pathways and triggered endoplasmic reticulum stress, as evidenced by the upregulation of proteasome subunits and unfolded protein response genes. Furthermore, silencing LvAQP11 delayed molting progression in the premolt stages, accompanied by the significant upregulation of molt-inhibiting hormone (LvMIH1/5) and downregulation of retinoic acid X receptor (LvRXR). The long-term silencing of LvAQP11 did not affect the weight gain rate (WGR) or the specific growth rate (SGR) but induced muscle fiber disorganization and significantly increased muscle water content. RNA sequencing identified enriched carbohydrate and chitin metabolism pathways, indicating disrupted cytoskeletal dynamics and extracellular matrix integrity. Through this study, we elucidate the crucial roles of LvAQP11 in osmoregulation, molting, and muscle integrity in L. vannamei, providing novel insights into the multifunctional nature of superaquaporins beyond water transport.

Exploring the Correlation Between Varied Serum Iodine Nutritional Levels and Anti-Thyroglobulin Antibodies - Qiuyi Song; Tingting Xu; Yu Wang; Hongyan Wei; Feng Tan; Yanting Chen; Fang Fang; Tingkai Cui; Ziyun Pan; Xiaohui Guo; Wen Chen; Jun Shen; et al. (Biological Trace Element Research, 2025)

From stem cells to pancreatic β-cells: strategies, applications, and potential treatments for diabetes - Xingrong Feng; Hongmei Zhang; Shanshan Yang; Daxin Cui; Yanting Wu; Xiaocun Qi; Zhiguang Su (Molecular and Cellular Biochemistry, 2025)

Cosmogenic radionuclide Beryllium-7 and Beryllium-10 characteristics and influencing factors in different natural climate regions, China - Xuke Liu; Yunchong Fu; Li Zhang; Yanting Bi; Yuda Cui; Guoqing Zhao (Science of The Total Environment, 2024)

Photothermal-driven soft actuator capable of alternative control based on coupled-plasmonic effect - Kechen Li; Qi Zhang; Xiyue Cui; Yiying Liu; Yanting Liu; Yuanyuan Yang (Chemical Engineering Journal, 2024)

Retraction Note: Downregulation of nicotinamide N-methyltransferase inhibits migration and epithelial-mesenchymal transition of esophageal squamous cell carcinoma via Wnt/β-catenin pathway - Yanyan Cui; Luyu Zhang; Wenjie Wang; Shanshan Ma; Hongtao Liu; Xingxing Zang; Yanting Zhang; Fangxia Guan (Molecular and Cellular Biochemistry, 2024)

Assessing the Interactive Effects of High Salinity and Stocking Density on the Growth and Stress Physiology of the Pacific White Shrimp Litopenaeus vannamei - Fei Liu; Jinfeng Sun; Jinnan Long; Lichao Sun; Chang Liu; Xiaofan Wang; Long Zhang; Pengyuan Hao; Zhongkai Wang; Yanting Cui; Renjie Wang; Yuquan Li (Fishes, 2024)
This study was conducted to evaluate the effects of high salinity combined with stocking density on Litopenaeus vannamei. Three salinity gradients, namely, 28 g/L, 36 g/L, and 44 g/L, and two stocking densities, namely, 300 and 600 shrimp/m3, were used to analyze the synergistic effect of high salinity and stocking density on the growth performance, digestibility, and energy budgets of L. vannamei. The experimental testing period lasted 45 days. The research results showed that a salinity level of 36 g/L was the most suitable salinity level for shrimp growth under both high and low stocking densities. The body weight, specific growth rate, and relative weight gain of the shrimp in the 36 g/L salinity group were significantly higher than those in the other two salinity groups under both high and low stocking densities. The high-density farming group with 600 shrimp/m3 exhibited a significant inhibition of shrimp growth compared to the low-density group under the same salinity conditions. The activities of amylase, lipase, and protease in the high-density-group shrimp gradually decreased with an increase in salinity, and the three digestive enzymes had the same overall effect of changing trends. This indicates that under high-density farming conditions, the increase in salinity is not conducive to the digestive function of shrimps. At the same time, the proportion of respiratory energy to feeding energy gradually decreased in the high-density group and with the increase in salinity. However, under the same salinity conditions, the higher the stocking density, the higher the energy consumed by respiration compared to the low-density group. In addition, the expression of the growth-related gene’s small nuclear ribonucleoprotein polypeptide G (SNRPG) under high stocking density was significantly lower than that in the low-density group at a salinity of 28 g/L, and ribosomal protein L7 (RPL7) expression was also significantly lower under high stocking density than that in the low-density group at a salinity of 44 g/L. The expression levels of molting-related genes retinoid X receptor (RXR), ecdysone receptor (ECR), and ecdysone-induced protein 75 (E75) were significantly higher in the 36 g/L salinity group compared with the other two salinity groups under high-stocking-density treatment. The findings indicate that the synergistic effects of salinity and stocking density have a significant impact on the growth of L. vannamei, and excessive salinity would inhibit its growth in the process of high-density culturing.

How Do Gene Expression Patterns Change in Response to Osmotic Stresses in Kuruma Shrimp (Marsupenaeus japonicus)? - Yuquan Li; Zhihao Zhang; Zhongkai Wang; Zhitong Deng; Ruiyang Zhao; Jinfeng Sun; Pengyuan Hao; Long Zhang; Xiaofan Wang; Fei Liu; Renjie Wang; Yanting Cui (Journal of Marine Science and Engineering, 2022)
Euryhaline crustaceans cope with external salinity changes by mechanisms of osmoregulation. In the current study, we first cloned and confirmed the ORF sequences of the ion-transportation-related genes Na+/K+-ATPase α subunit (NKAα), cytoplasmic carbonic anhydrase (CAc), and V-type H+-ATPase G subunit (VHA-G), and water channels of aquaporins (AQP3, AQP4, and AQP11) from kuruma shrimp (Marsupenaeus japonicus). Further tissue expression patterns showed a higher expression of MjAQP4, MjCAc, MjNKAα, and MjVHA-G in the gills, as well as a higher expression of MjAQP3 and MjAQP11 in the intestine and muscle, respectively. Then, qPCR analysis was used to assess the mRNA expression levels of those osmoregulatory genes in both post-larvae and adult shrimp when they were exposed to acute salinity stress or salinity acclimation. The results revealed significantly decreased expression levels of MjAQP3, MjAQP11, MjNKAα, and MjCAc, and higher expression levels of MjAQP4 and MjVHA-G when the post-larvae shrimp were directly subjected to 10‰ or 50‰ salinity. Moreover, similar expression patterns were also observed in the post-larvae shrimp during the accommodation to 10‰ or 50‰ salinity. As to the adult shrimp, significantly higher expression levels of those genes were observed in the gills after exposure to 10‰ salinity, whereas only the expression levels of MjAQP3, MjAQP11, and MjNKAα were up-regulated in the gills at 40‰ salinity. In contrast, the expression of MjVHA-G was significantly decreased at 40‰ salinity. Finally, during the acclimation to 10‰ salinity, the expression levels of MjAQP3, MjAQP11, and MjNKAα were also significantly elevated, while the expression of MjCAc was significantly decreased in the gills. In addition, the expression levels of MjAQP3, MjAQP4, MjCAc, and MjVHA-G were significantly decreased in the gills during the acclimation to 55‰ salinity. The findings of the study suggest that the examined genes are critical for the adaptation of aquatic crustaceans to changing environmental salinity. Our study lays as the foundation for further research on osmoregulation mechanisms in M. japonicus.

Morphological and histological changes in the brains of turbot (Scophthalmus maximus) with gonadal development - Chunyan Zhao; Liang Chi; Yongshuang Xiao; Bing Li; Yunliang Lu; Yanting Cui; Wenqi Wang; Jun Li (Acta Oceanologica Sinica, 2022)

Transcriptome Analysis of Pacific White Shrimp (Litopenaeus vannamei) Under Prolonged High-Salinity Stress - Yuquan Li; Yigeng Chen; Yanting Cui; Min Shen; Renjie Wang; Zhongkai Wang (Journal of Ocean University of China, 2022)

Aquaporins in Pacific White Shrimp (Litopenaeus vannamei): Molecular Characterization, Expression Patterns, and Transcriptome Analysis in Response to Salinity Stress - Zhongkai Wang; Yigeng Chen; Cong Wang; Nannan Zhao; Zhihao Zhang; Zhitong Deng; Yanting Cui; Renjie Wang; Yuquan Li (Frontiers in Marine Science, 2022)
Aquaporins (AQPs) are integral membrane proteins that facilitate the transport of water and small solutes across cell membranes. These proteins are vital for maintaining water homeostasis in living organisms. In mammals, thirteen aquaporins have been characterized, but in crustaceans, especially penaeid shrimp, the diversity, structure, and substrate specificity of these membrane channel proteins are largely unknown. We here presented the three types of AQPs from Litopenaeus vannamei based on genome and transcriptome sequencing. Phylogenetic analysis showed that each AQP separately represented members of aquaglyceroporins, classical aquaporins, and unorthodox aquaporins, thus they were named as LvAQP3, LvAQP4, and LvAQP11. The LvAqp4 was mostly expressed in hepatopancreas, stomach, and gill, meanwhile LvAqp3 and LvAqp11 were separately predominantly expressed in intestine and muscle, respectively. To investigate possible roles of aquaporins in osmoregulation, mRNA expression changes in mainly expressed tissues were analyzed after acute exposure or long-term acclimation to different salinities. The results revealed that the expression levels of aquaporins genes were significantly decreased in most tissues (except hepatopancreas) under salinity stress, though the expression patterns were variable among isoforms and tissues. Moreover, comparative transcriptome analysis indicated the combination roles of aquaglyceroporin and amino acid metabolism related genes and pathways in response to acute salinity changes in the intestine. This study opened new windows for future investigations and provided new insights into the role of aquaporins in osmoregulation in L. vannamei .

Activation of AMPK inhibits Galectin-3-induced pulmonary artery smooth muscle cells proliferation by upregulating hippo signaling effector YAP - Qianqian Zhang; Wenge Li; Yanting Zhu; Qingting Wang; Cui Zhai; Wenhua Shi; Wei Feng; Jian Wang; Xin Yan; Limin Chai; Yuqian Chen; Cong Li; et al. (Molecular and Cellular Biochemistry, 2021)

Inhibition of Breast Cancer Resistance Protein (BCRP) by Ko143 Can Affect Pharmacokinetics of Enrofloxacin in Exopalaemon carinicauda - Qianqian Zhai; Yang Xu; Cuiping Li; Yanyan Feng; Yanting Cui; Li Ma; Jian Li (Journal of Ocean University of China, 2020)

Correction to: Downregulation of nicotinamide N-methyltransferase inhibits migration and epithelial-mesenchymal transition of esophageal squamous cell carcinoma via Wnt/β-catenin pathway - Yanyan Cui; Luyu Zhang; Wenjie Wang; Shanshan Ma; Hongtao Liu; Xingxing Zang; Yanting Zhang; Fangxia Guan (Molecular and Cellular Biochemistry, 2020)

Acute response of Pacific white shrimp Litopenaeus vannamei to high-salinity reductions in osmosis-, metabolism-, and immune-related enzyme activities - Min Shen; Yanting Cui; Renjie Wang; Tiantian Dong; Haibin Ye; Shusheng Wang; Ranghui Fu; Yuquan Li (Aquaculture International, 2020)

RETRACTED ARTICLE: Downregulation of nicotinamide N-methyltransferase inhibits migration and epithelial-mesenchymal transition of esophageal squamous cell carcinoma via Wnt/β-catenin pathway - Yanyan Cui; Luyu Zhang; Wenjie Wang; Shanshan Ma; Hongtao Liu; Xingxing Zang; Yanting Zhang; Fangxia Guan (Molecular and Cellular Biochemistry, 2019)

Iodine Nutrition and Thyroid Function in Pregnant Women Exposed to Different Iodine Sources - Yanting Chen; Wen Chen; Cong Du; Lili Fan; Wei Wang; Min Gao; Yixin Zhang; Tingkai Cui; Yunmeng Hao; Elizabeth N. Pearce; Chongdan Wang; Wanqi Zhang (Biological Trace Element Research, 2019)

Association between Val66Met polymorphisms in brain-derived neurotrophic factor gene and asthma risk: a meta-analysis - Xinming Xie; Yanting Zhu; Jiaojiao Zhang; Cui Zhai; Wei Feng; Yilin Pan; Lu Liu; Xiaofan Su; Lan Yang; Manxiang Li (Inflammation Research, 2015)

Effect of heat stress and recovery on viability, oxidative damage, and heat shock protein expression in hepatic cells of grass carp (Ctenopharyngodon idellus) - Yanting Cui; Bo Liu; Jun Xie; Pao Xu; H-Michael Habte-Tsion; Yuanyuan Zhang (Fish Physiology and Biochemistry, 2014)

Effect of enrofloxacin and emodin on heat-shock proteins’ expression in hepatic cells of grass carp (Ctenopharyngodon idellus) - Yanting Cui; Bo Liu; Jun Xie; Pao Xu; Yuanyuan Zhang; Jianhua Ming (Aquaculture International, 2014)